Development and characterization of human brown adipose spheroids - Bonet Morata, Natalia (My University, 2025)
The global obesity epidemic poses a major public health crisis linked to obesity-related metabolic diseases. Current obesity treatments face limitations in effectiveness and adherence, which has led to a growing interest in targeting brown adipose tissue (BAT), a thermogenic tissue whose activation is related to better cardiometabolic health, as a novel therapeutic approach. This thesis focuses on the development and characterization of human brown adipose spheroids (3D models) from the stromal vascular fraction obtained from the supraclavicular BAT of healthy adult volunteers. It aims to create and validate brown adipose (BA) spheroids as a physiologically relevant model for studying adipose tissue, offering significant potential for drug screening, disease modeling, and personalized medicine. To achieve this, cells were isolated from the SVF from the BAT biopsies and seeded to generate 2D or 3D brown and white adipose (WA) cell culture models, either undifferentiated or differentiated. Morphological tests, a lipolysis assay and gene expression analysis were then conducted. The results showed that BA spheroids increase in size, probably due to their adipocyte growth and lipid accumulation. Gene expression analyses showed that spheroids differentiate correctly and are more thermogenic than WA spheroids. Also, both differentiated WA and BA spheroids show proper adipogenic function. Moreover, the lipolysis assay demonstrated that BA spheroids present a higher lipolytic capacity than WA spheroids. These results confirm the potential of BA spheroids as a tool for studying BAT biology, but more participants should be included in the study to further validate the model.
Keywords: brown adipocytes, spheroids, morphological analysis, gene expression, lipolysis